CLINICAL-TECHNOLOGICAL CONSIDERATIONS REGARDING THE REALIZATION OF PARTIALLY REMOVABLE SKELETALE TITANIUM PROSTHESES - Magda-Ecaterina Antohe; Doriana Agop-Forna; Roxana Ionela Vasluianu; Cosmin Crețu; Daniel Paval; Ovidiu Stamatin; Norina Consuela Forna (Romanian Society of Oral Rehabilitation, 2023)
The progress recorded in the technology of skeletale removable prostheses, with immediate reflection in clinical use, draws attention to these materials, the specialized literature covering practically all areas of their use in dentistry.The purpose of the study is represented by the identification of the technological particularities of making skeletonized removable partial prostheses made of Titanium in accordance with the particularity of the clinical cases and the technological line approached. A number of 10 titanium skeletal prostheses anchored in the classical register as well as in the modern register were made by using attachments as elements to maintain support and stabilization. The high reactivity of molten titanium (as well as that of crystallized titanium but at high temperatures) with oxygen from the packing table and/or from the working environment or the material of the crucible, as the case may be, with other chemical components thereof, make the surface of the cast part to appear a reaction zone with a thickness of 25-200mm, called the a-case layer. The realization of partially removable titanium prostheses is a particularly important step in achieving the biocompatibility and suppleness of these components with an impact in terms of patient comfort.